Structure elucidation of the novel synthetic cannabinoid Cumyl‐Tosyl‐Indazole‐3‐Carboxamide (Cumyl‐TsINACA) found in illicit products in Germany. Issue 8 (9th April 2022) - Pulver, Benedikt; Schönberger, Torsten; Weigel, Diana; Köck, Matthias; Eschenlohr, Yvonne; Lucas, Tobias; Podlesnik, Nika; Opatz, Till; Dreiseitel, Wolfgang; Pütz, Michael; Schäper, Jan; Jacobsen‐Bauer, Andrea; et al.
Abstract: New chemical moieties continue to appear in synthetic cannabimimetics (SC), the largest group of new psychoactive substances in the EU. We describe the first comprehensive characterisation of the novel SC Cumyl‐Tos yl‐I n dazole‐3‐Ca rboxa mide (Cumyl‐TsINACA) ( N ‐[2‐phenylpropan‐2‐yl]‐1‐tosyl‐1 H ‐indazole‐3‐carboxamide) from seized case samples. Structure elucidation was performed within the EU‐project ADEBAR plus to facilitate confident identification by other researchers and practitioners worldwide. Characteristic MS fragmentations include the cleavage of the sulfonamide bond (S‐N), the aryl sulfone bond (C‐S) and the elimination rearrangement of SO2 in the side chain. Cumyl‐TsINACA is a full receptor agonist at h CB1 (Emax  = 228%) with very weak binding affinity ( K i  = 292 nm ) and low functional activity (EC50  = 31 μm ). Thermal degradation of Cumyl‐TsINACA was observed under GC conditions. The degree to which the tosyl side chain is cleaved due to pyrolysis primarily depends on solvent, the use of glass wool in the liner and injector temperature. The determination of the constitution by NMR spectroscopy was ambiguous due to the high number of neighbouring, non‐proton‐bearing atoms. Therefore, other possible structures compatible with the NMR correlations were generated using the WebCocon software. The unambiguous structural evidence was finally obtained by spectra comparison after the synthesis of Cumyl‐TsINACA. The low thermal stability, as well as the low affinity and potency, renders this compound unfavourable for the use as a psychoactive substance. Thus, we do not expect widespread adoption of this SC. Abstract : Structure elucidation of the novel synthetic cannabinoid Cumyl‐TsINACA from seized case samples is described. Additionally, analytical characteristics and pharmacological properties are discussed.